Elaboration, structure, microstructure and magnetic properties of soft Fe80Ni20 nanomaterials elaborated by high energy ball milling. Issue 3 (24th March 2014) - Guittoum, Abderrahim; Lamrani, Sabrina; Bourzami, Abdelkader; Hemmous, Messaoud; Souami, Nassim; Weber, Wolfgang
Abstract : The aim of the present work is to elaborate nanocrystalline soft Fe80 Ni20 powders and to study the relationship between their magnetic behaviour and structural changes after different milling times. A series of Fe80 Ni20 powders were elaborated by the mechanical alloying process for milling time ranging from 3 to 25 h. X-ray diffraction results showed that nickel dissolved in the iron lattice and formed a complete cubic centered (bcc) solid solution after 10 h of milling time. As the milling time increases from 0 to 25 h, the lattice parameter increases from 0.28610 nm for pure Fe to 0.28670 nm, the grain size decreases from 75 to 11 nm, while the mean level of strain increases from 0.09% to 0.5%. It is found that the saturation magnetization increases while the coercivity decreases when the milling time increases. The increase of saturation magnetization and decrease of coercivity are attributed to the decrease of the grain size with milling time. We have shown that nanocrystalline Fe80 Ni20 powders exhibit a soft magnetic behaviour.